KAPASITAS VOLUME OKSIGEN MAKSIMAL PADA MAHASISWA PROGRAM STUDI PENDIDIKAN JASMANI ANGKATAN 2016 - Dina, Suci Rahma; Hidasari, Fitriana Puspa; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe increase in the number of semester lectures resulted in a reduction in practical courses involving student physical activity. The reduced physical activity of these students affected their fitness level. This can be measured from the maximum capacity of oxygen volume intake by students during lectures. The purpose of this study was to measure the maximum oxygen volume capacity intake by physical education students. The method used in this study was descriptive, of which the data were analyzed using a qualitative analysis model. The research subjects were the year 2016 physical education students, of which 66 students from two classes were taken as the sample. The data were collected using a Bleep Test. The findings showed that the maximum capacity of the oxygen volume intake was found in several categories. Nine students were in the low category, fifty-one in a medium category, and six in a high category. The maximum and minimum capacity of oxygen intake was respectively 51.10 and 32.54. Therefore, Finally, this study summarizes physical education students’ cardiorespiratory endurance or fitness, of which the Vo2 Max was categorized medium with a percentage of 65.15%.Keywords: Vo2Max, oxygen intake, Physical Education Students.